2014
DOI: 10.1007/s00535-014-0998-z
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical responses to bezafibrate improve long-term outcome in asymptomatic patients with primary biliary cirrhosis refractory to UDCA

Abstract: These results suggested that normalization of ALT levels with additional bezafibrate treatment significantly decreased the rate of occurrence of liver-related symptoms in asymptomatic PBC patients with suboptimal response to UDCA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 33 publications
2
39
1
Order By: Relevance
“…Bezafibrate was more effective in non‐cirrhotic patients (liver stiffness value <14.4 kPa), albeit not significantly. Ursodeoxycholic acid is the drug used most frequently for PSC, and combination therapy using UDCA and bezafibrate is effective for primary biliary cholangitis . However, in this analysis, concomitant use of UDCA tended to be associated with bezafibrate inefficacy.…”
Section: Discussionmentioning
confidence: 63%
“…Bezafibrate was more effective in non‐cirrhotic patients (liver stiffness value <14.4 kPa), albeit not significantly. Ursodeoxycholic acid is the drug used most frequently for PSC, and combination therapy using UDCA and bezafibrate is effective for primary biliary cholangitis . However, in this analysis, concomitant use of UDCA tended to be associated with bezafibrate inefficacy.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, when we calculated the HR of BF treatment after IPTW adjustment to reduce background selection bias, BF treatment significantly reduced the risk of liver transplantation or liver‐related death in patients with normal serum bilirubin. Furthermore, our previous long‐term (6.1 ± 3.4 years) observational study using 835 asymptomatic PBC patients from a Japanese nationwide survey showed that ALT response to BF treatment was significantly associated with the occurrence of liver‐related symptoms, which also suggests that the addition of BF to UDCA monotherapy improves the long‐term prognosis of PBC patients.…”
Section: Discussionmentioning
confidence: 87%
“…Fibrates, including bezafibrate and fenofibrate, may be useful for treating asymptomatic patients with PBC who exhibit inappropriate response to UDCA[179-183]. A nationwide retrospective survey in Japan demonstrated that normalizing serum ALT concentrations with accessional bezafibrate therapy observably reduced the occurrence of hepatic illness-associated clinical signs in symptomless patients, with PBC responding incompletely to UDCA[179].…”
Section: Therapy Of Pbcmentioning
confidence: 99%
“…A nationwide retrospective survey in Japan demonstrated that normalizing serum ALT concentrations with accessional bezafibrate therapy observably reduced the occurrence of hepatic illness-associated clinical signs in symptomless patients, with PBC responding incompletely to UDCA[179]. Moreover, long-term combined bezafibrate and UDCA treatment in PBC not only observably ameliorated the Mayo risk score and serum concentrations of ALP, but also observably elevated the serum concentrations of creatinine[180].…”
Section: Therapy Of Pbcmentioning
confidence: 99%